Kampanye dan Akses Media Terhadap Kebijakan Energi Baru dan Terbarukan dalam Perspektif Mahasiswa Di Sumatera Utara - Mickhael Rajagukguk (Expose: Jurnal Ilmu Komunikasi, 2022)
This research examines the knowledge of college students about the development of new and renewable energy in Indonesia. Furthermore, this study intends to see how the college students perceive the government performance, which has associated with the effectiveness of what types of media are appropriate in increasing the knowledge of the college students about new and renewable developments energy in Indonesia. This research method uses a quantitative descriptive method. The population in this study is the younger generation who are students on campuses in North Sumatra. The research sample was 146 respondents. The sampling process uses quota sampling. The data collection technique was carried out using a questionnaire instrument. The analysis used in this research is the single table and cross-table analysis. This study indicated that college students still did not fully understand what new and renewable energy is. In addition, students' knowledge of policies related to New and Renewable Energy is also in the low category. Students think that the government's performance is still poor, and it is necessary to conduct a campaign and involve the mass media.